2020
DOI: 10.1155/2020/4830418
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2/PGC1α Pathway Regulates Antioxidant and Proteasomal Activity to Alter Cisplatin Sensitivity in Ovarian Cancer

Abstract: Drug resistance remains a barrier in the clinical treatment of ovarian cancer. Proteasomal and antioxidant activities play important roles in tumor drug resistance, and increasing evidence suggests the existence of an interaction between antioxidant and proteasomal activities. However, the mechanism of the synergistic effects of proteasomal activity and antioxidation on tumor drug resistance is not completely clear. In this study, we compared two ovarian cancer cells, A2780 and SKOV3 cells. Among them, SKOV3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Nrf2 is a key redox regulator. HO-1 and GCLC are located downstream of Nrf2 and play important roles in intracellular redox balance as antioxidant enzymes ( Bao et al, 2014 ; Silva et al, 2019 ; Deng et al, 2020 ; Ghosh et al, 2021 ). Some reports showed the balance between Nrf2/GSH antioxidant pathway and DNA repair might modulate cisplatin resistance in cancer cells ( Qiu et al, 2020 ; Ghosh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a key redox regulator. HO-1 and GCLC are located downstream of Nrf2 and play important roles in intracellular redox balance as antioxidant enzymes ( Bao et al, 2014 ; Silva et al, 2019 ; Deng et al, 2020 ; Ghosh et al, 2021 ). Some reports showed the balance between Nrf2/GSH antioxidant pathway and DNA repair might modulate cisplatin resistance in cancer cells ( Qiu et al, 2020 ; Ghosh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the important role of redox modification of signaling pathways in the pathogenesis of OC, including the Keap1-Nrf2-ARE, PI3K/AKT/mTOR, Wnt/β-catenin, and Notch pathways [100][101][102][103].…”
Section: Os-mediated Alterations Of Signaling Pathways In Ocmentioning
confidence: 94%
“…In addition, inhibiting the production of proteasomes promotes the translocation of Nrf2 into the nucleus via the Keap1/Nrf2 pathway, resulting in drug resistance in OC cells. Nrf2 and peroxisome proliferator-activated receptor-γ coactivator 1α (PGC1α) can synergistically regulate antioxidant functions and mitochondrial functions, thus regulating the maintenance of proteasome activity and affecting the sensitivity of OC cells to chemotherapy agents [101]. Oxidative Medicine and Cellular Longevity…”
Section: Keap1-nrf2mentioning
confidence: 99%
“…The measured values were expressed as a ratio by comparing them to the control group values. More details for WB and sqRT-PCR were described previously [ 36 ]. In brief, cells were lysed in radio immunoprecipitation assay (RIPA) lysis buffer (P0013B, Beyotime).…”
Section: Methodsmentioning
confidence: 99%